Pengaruh Suhu Pengeringan Terhadap Aktivitas Antioksidan Dan Karakteristik Teh Celup Herbal Daun Mint (Mentha piperita L.) - Sucianti, Asti; Yusa, Ni Made; Sughita, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This study aims to find out the effect of drying temperature on antioxidant activity and characteristics of mint leaf herbal tea bags and to know the drying temperature that can produce herbal tea bags mint leaves with the highest antioxidant activity and best characteristics. The design used in this study is a Complete Randomized Design with drying temperature treatment consisting of 5 levels of 5 levels namely 50 o C, 55 o C, 60 o C, 65 o C, and 70 o C. This study was repeated three times so that 15 experimental units were obtained. The data obtained were analyzed with fingerprints and if the treatment had any real effect continued with Duncan's test. Parameters tested in this study include water content, yield, total phenol levels, total flavonoid levels, antioxidant and IC50 activity, and sensory characteristics. The results showed herbal teabag mint leaves with a drying temperature of 50 o C is the best treatment based on water content value of 7,52%, yield 14,16%, total phenol 6,50 mgGAE/g, total flavonoids 5,15 mgGAE/g, antioxidant activity 54,55% with IC50 value of 86,18 ppm, yellow color, very characteristic aroma of mint leaf tea and preferred, fresh mint flavor, and overall acceptance preferred.